The technology of high technical level of melting and refining is the basis for production of high-quality casted slug at the Belorussian metallurgical works - V. I. Timoshpolskii (Литьë и металлургия)
Іп the article there is given the analysis of the\ technology of melting and out-offumace processing with the purpose of receiving the high-quality metal production. There is shown, that the existing technology of the steelmaking in conditions of RUP ”Belorussianmetallurgical works ” is directed on creation of scientific sorts of steel with the minimally possible presence of detrimental impurities: sulfur and phosphorus.